Closeness of Late Adolescents’ in Javanese Families: A Qualitative Study of Parent-Child Relation - Agustin Erna Fatmasari; Niken Fatimah Nurhayati (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
Closeness is a quality predictor of a harmonious parent-child relationship. Closeness demonstrates a mutually influencing parent-child relationship involving physical, mental and emotional aspects. This research aims to explore the dynamic of closeness in parent-child relationships between parents and their late adolescents’ sons and daughters in Javanese families. The research uses qualitative method through a thorough interview. Research respondents were six late adolescents’ in their undergraduate studies of which were selected based on the fulfillment of criteria. The qualitative analysis uses a phenomenologis perspective. The research results show the strongest reasons for being close to their fathers are because fathers are understanding, caring, and guiding. The strongest reasons for being close to their mothers are because they are understanding, caring and accompanying. Fathers-mothers understand and care based on the father-mother role in Javanese families, referred to as asih, fathers guide (asah), and because mothers accompany (asuh). Closeness with fathers occurs more in informal and recreational activities, whereas closeness with mothers are related to household tasks. The interesting findings of this study are an external condition that influence parent child relation to be closer or otherwise. External condition that influence closeness are parent approach to their children, technological advancement, differences in vision in choosing a partner, and unfortunate experiences with one parent.